Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1017/s0950268804003103
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the mortality rate of hepatitis C using multiple data sources

Abstract: The New York State hospital discharge database and the multiple cause-of-death file were used to estimate the mortality rate of hepatitis C in New York State excluding New York City in 1997. The mortality rate with hepatitis C was severely underestimated when each data source was used alone. Applying the capture recapture method using the hospital discharge database and the multiple cause-of-death file appears to be an efficient method to estimate the mortality rate with hepatitis C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Very few surveys are published on HBV and HCV infection-related mortality. One study from the United States (New York state excluding New York City) was based on a population of 491 deaths identified in 1997 using multiple data sources (hospital discharge database and cause-of-death file) and found an HCV infection-related mortality rate of 4.5 per 100,000 (6.1 for men and 2.9 for women) [22]. These results correlate well with the data from the present study.…”
Section: Discussionsupporting
confidence: 87%
“…Very few surveys are published on HBV and HCV infection-related mortality. One study from the United States (New York state excluding New York City) was based on a population of 491 deaths identified in 1997 using multiple data sources (hospital discharge database and cause-of-death file) and found an HCV infection-related mortality rate of 4.5 per 100,000 (6.1 for men and 2.9 for women) [22]. These results correlate well with the data from the present study.…”
Section: Discussionsupporting
confidence: 87%
“…The present study has several limitations. First, we used NDI data (based on death certificates) to classify deaths as liver-related, therefore there may have been misclassification of the cause of deaths [16,53]. We expect that this misclassification would be nondifferential with regard to HCV status, although it is possible that the person coding the death certificate might be more likely to select a liver-related cause given a range of possible contributing causes of death, which would bias in favor of the observed association.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that a large portion of the unspecified cirrhosis deaths were in fact alcohol-related (Parrish et al, 1993). Moreover, the detection of HCV has not been comprehensive for various reasons (Manos et al, 2008; Wu et al, 2005). Third, data from death certificates lack information on etiological factors other than alcohol and HCV.…”
Section: Discussionmentioning
confidence: 99%